1997
DOI: 10.1359/jbmr.1997.12.11.1883
|View full text |Cite
|
Sign up to set email alerts
|

Bone Density Variation and Its Effects on Risk of Vertebral Deformity in Men and Women Studied in Thirteen European Centers: The EVOS Study

Abstract: In Europe there is a 3-fold variation, according to geographical center, in risk of vertebral deformity in men and women over the age of 50. We investigated the relationship between bone density, as assessed by dual-energy X-ray absorptiometry (DEXA) of the spine and hip and prevalent vertebral deformities in 13 of the 36 centers participating in the European Vertebral Osteoporosis Study (EVOS). Each center recruited an age-stratified sample of men and women aged 50 years and over, and of those who agreed to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
85
2
9

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(111 citation statements)
references
References 33 publications
9
85
2
9
Order By: Relevance
“…The magnitude of the geographic variation of fractures within CaMos was smaller than noted in previous international studies [2,5,11,25], but comparable to the magnitude of variation found in other North American studies [33,34]. The pattern of geographic variation in incident low-trauma fracture was similar to the pattern of prevalent low-trauma fracture for both men and women.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The magnitude of the geographic variation of fractures within CaMos was smaller than noted in previous international studies [2,5,11,25], but comparable to the magnitude of variation found in other North American studies [33,34]. The pattern of geographic variation in incident low-trauma fracture was similar to the pattern of prevalent low-trauma fracture for both men and women.…”
Section: Discussionsupporting
confidence: 69%
“…Results from the European Prospective Osteoporosis Study (EPOS) have reported that BMD is related to vertebral deformity and that population geographic variation in vertebral deformity is partially explained by variation in BMD measurements [24,25]. While BMD was a predictor of vertebral deformity in this study, the geographic variation of BMD was not concordant with the geographic variation of vertebral deformity in women and only weakly concordant in men.…”
Section: Discussioncontrasting
confidence: 60%
“…The prevalence of VFs in acromegalic patients largely exceeded the prevalence in the control population, in all age groups (25). In addition, large European population-based cohort studies also report a much lower prevalence of VFs in both men and women (28)(29)(30)(31)(32), comparable to the findings in the Dutch reference cohort. Our findings, based on the scoring of two independent scorers and confirmed by an experienced radiologist, demonstrate that the prevalence of VFs in acromegalic women, but even more so in acromegalic men, exceeds the reported prevalence of VFs in the general population, including the Dutch population.…”
Section: Discussionmentioning
confidence: 55%
“…Sli~no tome, rezultati studije EVOS (engl. European Vertebral Osteoporosis Study) su u oba spola pokazali jednak odnos izme|u rizika prijeloma kralje{ka i BMD-a kralje`nice, odnosno BMD-a proksimalnog dijela bedrene kosti (9).…”
Section: U^estalost Osteoporozeunclassified